2006
DOI: 10.1080/02770900601034304
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Health in Canadian Asthmatics

Abstract: Asthma is a chronic respiratory disease affecting approximately 8% of the Canadian population. Being physically active may assist in management of the disease and lead to improvements in overall health. The purpose of this study was to determine whether involvement in physical activity (PA) influenced self-reported measures of health in asthmatics. The sample included 4272 asthmatic men and 6971 asthmatic women who participated in the Canadian Community Health Survey cycle 2.1. The median age for this group fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 16 publications
1
14
0
1
Order By: Relevance
“…They proposed that physical activity should be widely recommended for patients with COPD in COPD guidelines 21. Our results were also in accordance with those from an asthma population in Canada,22 where those with good self-reported health are more physically active. Pitta et al, also showed that encouragement to be more active in daily life is an important part of the management of patients with COPD 23…”
Section: Discussionsupporting
confidence: 90%
“…They proposed that physical activity should be widely recommended for patients with COPD in COPD guidelines 21. Our results were also in accordance with those from an asthma population in Canada,22 where those with good self-reported health are more physically active. Pitta et al, also showed that encouragement to be more active in daily life is an important part of the management of patients with COPD 23…”
Section: Discussionsupporting
confidence: 90%
“…In 2006, Dogra and Baker examined a group of asthmatics and found that physically active asthmatics had significantly greater SRMH and fewer chronic physical/mental chronic conditions [42]. In 2007, a descriptive study by Park and Knudson report that people with medically unexplained physical symptoms (MUPS) were more likely than those without MUPS to rate their mental health as fair or poor [43].…”
Section: Resultsmentioning
confidence: 99%
“…Better self-perceived health is associated with higher levels of physical activity in the general population [28,39,51] and adults with asthma [27,52]. This is not surprising, as physical activity is known to positively influence physical and psychosocial aspects of health.…”
Section: Discussionmentioning
confidence: 89%